Exploring secondary teachers' perspectives on implementing competency‐based education. Issue 4 (5th December 2021) - Rogers, Audrey P.
Abstract: Background: Competency‐based education (CBE) has been implemented to varying degrees in the last several decades. New Hampshire has led the way in policy changes to promote its adoption. However, there has been a tension between the goals of the initiative and how teachers' beliefs inform implementation. Aims: The purpose of this study was to take an in‐depth examination of NH middle and high school teachers' beliefs around CBE and its impact on their classroom practices and students. Methods: This study utilized a sequential explanatory mixed methods approach through survey data and follow‐up interviews and observations in three NH districts. The Concerns‐Based Adoption Model (CBAM) conceptual framework served as a lens to analyze data. Results: The three districts revealed varying levels of implementation mitigated in part by teachers' beliefs. Participants in the district with more advanced CBE implementation described the largest perceived impact of transformed pedagogical practices and an ability to persist with or without administrative support. Some participants noted an increase in students' access to the curriculum and a decrease in students' anxiety and feelings of being judged. Discussion: Findings suggested that contextual factors informed participants' beliefs and subsequent practices. Districts with administrative support revealed more widespread impact on teachers and students. Structural supports promoting implementation also supported teachers' integration of CBE principles. Conclusion: District leaders need to attend to teachers' beliefs to offer differentiated professional development and build on CBE elements already in place. Further study in how CBE principles may reduce student anxiety is timely and needed.